Asset markets with insider trading disclosure rule and reselling constraint : an experimental analysis - Halim, Edward (2022)
We investigate the impact of compulsory insider-trading disclosure and its combination with a mandatory holding rule on price predictability and asset mispricing. We modify the dynamic price-adjustment model to account for insiders’ private information. Our results show that insiders produce weakly-characterized price signals that induce a less than proportional price adjustment to the changes in the dividend value, in both markets with disclosure rule and holding requirement, in comparison with unregulated markets. A shift in insiders’ strategies from information-motivated to liquidity-motivated trading appears to fuel the impairment of price predictability in regulated markets. The exacerbation of asset mispricing in markets with holding restriction is characterized by a growth in the speculative transactions and loss-making trading proposals.